(untitled) (Revista Electrónica Calidad en la Educación Superior, 2021)
The sociodemographic study of the university student population allows us to visualize factors that can influence success in the educational system. The purpose of this article is to identify the characteristics of the student population in the Teaching of Natural Sciences and who studied subjects during the II four-month period of 2018. Through a comparative analysis of demographic, social and economic variables, a survey was used with a semi-quantitative approach (open and closed questions); the sample was 185 students. The survey was prepared and validated by experts in the area of ​​science and related education (Chemistry, Physics and Biology). According to other studies carried out in Costa Rica, the sociodemographic characteristics obtained in this study are not significantly divergent in aspects such as: access to higher education by gender, age ranges and type of school of origin. On the other hand, it was found that paid employment favors male gender and child rearing is assigned to women, which confirms traditional gender roles. The study allowed a greater understanding of the characteristics of the student body, which will serve as input to generate improvements in the educational program.